Imaging myocardial scar in hypertrophic cardiomyopathy: advances in CMR and CT - Sclafani, Matteo; Perrotti, Chiara; Salerno, Luigi; Muthukkattil, Melwyn Luis; Lustri, Camilla; Cristofari, Gabriele; Falasconi, Giulio; Musumeci, Maria Beatrice; Penela, Diego; Saglietto, Andrea; Iannaccone, Agnese; Barbato, Emanuele; et al. (Frontiers in Cardiovascular Medicine, 2025)
Myocardial scarring is a hallmark of hypertrophic cardiomyopathy (HCM) and a major driver of adverse outcomes, including sudden cardiac death and heart failure progression. The fibrotic substrate in HCM is complex, encompassing both replacement and interstitial fibrosis, often accompanied by myocardial disarray. Advanced cardiovascular imaging enables detailed scar characterization, which is crucial for risk stratification and personalized management. Cardiovascular magnetic resonance (CMR) is the gold standard for non-invasive fibrosis assessment. Techniques such as late gadolinium enhancement, myocardial mapping of T1 and T2 relaxation properties, and diffusion tensor imaging provide complementary insights into scar burden and architecture. Cardiac computed tomography (CT) is an emerging modality with increasing clinical relevance. Delayed iodine enhancement and CT-derived extracellular volume mapping offer a valuable alternative for scar assessment, particularly when CMR is contraindicated. This review highlights the role of multimodality imaging in assessing myocardial scar in HCM, with a focus on CMR and CT, and explores their clinical implications.